A Tool for "Real-Time" Formative and Summative Assessments of Milestones and Surgical Skills. (October 2015) - Connolly, AnnaMarie; De La Cruz, Jacquia; Sullivan, Stephanie
Abstract : OBJECTIVE: To develop a web-based tool for "real time, " venue-based: 1) Formative assessment of milestones and surgical skills; 2) Summative review of milestone level attainment and surgical skill competency. METHODS: Software engineers were engaged to develop this web-based application. All Accreditation Council for Graduate Medical Education-required obstetrics and gynecology milestones and select surgical procedures were incorporated into the application. For milestones, each item within each level of each milestone set was programmed such that "yes/no" responses could be recorded. Similarly, surgical procedures were divided into roughly 10 "key" steps and each step programmed with responses ranging from novice to expert. Overall surgical procedural ability was also programmed into this application. RESULTS: Over 6 months, the web-based tool was developed. With a secure log-in, the program directs users to generate either new formative feedback or review past summative feedback. All obstetrics and gynecology milestones were successfully incorporated into the program with formative and summative assessments possible for each element of each milestone set. Likewise, all selected surgical procedures were successfully incorporated with successful assignment of competency level to each "key" step as well as to each procedure overall. Software engineers actively ensured consistency of application function, operational integrity, and application efficiency. CONCLUSION: A web-based tool was successfully developed for "real-time, " venue-based formative and summative assessment of milestones and surgical skills. Tool implementation could facilitate meaningful feedback between residents and teachers as well as provide valuable information on resident progress with milestone level attainment and surgical skills competency. Future directions include testing in obstetrics and gynecology residency programs and this work is underway.